Evaluación de la eficacia de la ozonoterapia como medida alternativa para el tratamiento de mastitis clínica bovina. - Campoverde Veintimilla, Jackson Estuardo (2020)
Livestock in Ecuador is considered as an economically profitable activity being a very common disadvantage in these farms the development of mastitic cadres. The present investigation was developed in the Motupe sector of the province of Loja, the objective of this research was to determine h consisting of 4 units, in doses of (A) 35 g / ml and (B) 40 g / ml in three applica tions, compared the effectiveness of ozone therapy as an alternative treatment against the use of antibiotics in the treatment of bovine clinical mastitis. Through the application of an ozonized solution administered intramammary. 12 experimental units were used, conforming 3 groups: A, B, C, eac to a conventional (C) control (application of antibiotic - Cobactan 2.5 %) in doses of 2ml / 50kg dose IM. The investigation consisted of 3 treatments with 3 repetitions every 24 h, for which 12 cows resulting from the Holstein crossing in dairy production were used with the presence of clinical mastitis proven by the CMT reactive test. The variables used were: degree of affection, effectiveness of the treatment in the NCS, cost-effectiveness. The results in the degree of affection in the pre-treatment statistically show no significant difference between the somatic cell averages in each of the groups formed by a rapid somatic cell test ”the Porta SCC”. The results in the effectiveness in the application of each treatment by means of an RCS showed that by means of a model (ANOVA); on day 1 it showed no sta- tistical difference (p = 0.7103), unlike the second day (p = 0.2968) and third day (p = 0.1862); obtaining a recovery percentage in both (T1) and (T3) of 50 % for both treatments and 25 % for (T2). In the economic part, the use of ozone turns out to be more feasible compared to the use of an antibiotic, the cost per unit being: USD 10.07 USD unlike T3, the cost being: USD 17.52. . Key words: Clinical Mastitis, Bovines, Ozone Therapy, Antibiotic